2007
DOI: 10.1016/j.neuron.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein Regulates Brain Apolipoprotein E and Cholesterol Metabolism through Lipoprotein Receptor LRP1

Abstract: Mutations in the amyloid precursor protein (APP) cause early-onset Alzheimer's disease (AD), but the only genetic risk factor for late-onset AD is the varepsilon4 allele of apolipoprotein E (apoE), a major cholesterol carrier. Using Cre-lox conditional knockout mice, we demonstrate that lipoprotein receptor LRP1 expression regulates apoE and cholesterol levels within the CNS. We also found that deletion of APP and its homolog APLP2, or components of the gamma-secretase complex, significantly enhanced the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
281
5
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(299 citation statements)
references
References 60 publications
7
281
5
2
Order By: Relevance
“…In contrast, overexpression of the LDLR in the brain decreases apoE levels, reflecting an increased metabolism of apoE (Kim et al 2009b). Similarly, conditional deletion of the Lrp1 gene in mouse forebrain neurons increases apoE levels (Liu et al 2007) and overexpression of a functional LRP1 minireceptor in mouse brain decreases brain apoE levels (Zerbinatti et al 2006). Although both LDLR and LRP1 play roles in brain apoE/lipoprotein metabolism, there are important differences between them.…”
Section: Lrp1 and Ldlr In Cellular And Brain Ab Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, overexpression of the LDLR in the brain decreases apoE levels, reflecting an increased metabolism of apoE (Kim et al 2009b). Similarly, conditional deletion of the Lrp1 gene in mouse forebrain neurons increases apoE levels (Liu et al 2007) and overexpression of a functional LRP1 minireceptor in mouse brain decreases brain apoE levels (Zerbinatti et al 2006). Although both LDLR and LRP1 play roles in brain apoE/lipoprotein metabolism, there are important differences between them.…”
Section: Lrp1 and Ldlr In Cellular And Brain Ab Metabolismmentioning
confidence: 99%
“…First, whereas LRP1 is highly expressed in neurons and to a lesser degree in glia, LDLR is more prominently expressed in glia than neurons (Rebeck et al 1993;Rapp et al 2006). Second, deletion of the Lrp1 gene in mouse forebrain neurons reduces brain cholesterol levels (Liu et al 2007), whereas cholesterol levels in Ldlr knockout mice are unchanged (Fryer et al 2005a). Third, apoE/lipoprotein particles secreted by astrocytes have higher affinity for LDLR than LRP1 (Fryer et al 2005a), whereas recombinant apoE (Narita et al 2002), apoE-enriched lipoprotein particles (Kowal et al 1990), and CSF-isolated HDL particles (Fagan et al 1996) bind more avidly to LRP1.…”
Section: Lrp1 and Ldlr In Cellular And Brain Ab Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Fe65 or Fe65-AICD complex interact with nuclear proteins such as Tip60, SET, CP2/LSF (13-15) and experimental evidence indicated that they could be involved in transcription activation (16)(17)(18)(19)(20). However, several studies raised the question of the specificity of this regulation; in particular, De Strooper and colleagues (21) demonstrated that ␥-secretase inhibitors, suppression of presenilins or APP/APLP2 do not induce any significant change in the expression levels of several candidate genes, whereas Fe65 appears to have a rather nonspecific effect on transcription.…”
mentioning
confidence: 99%
“…The targets that have been reported to be up-regulated included the metastasis suppressor KAI1/CD82 (60,61), the tumor suppressor TP53 (62), the A␤-degrading enzyme neprilysin (NEP) (42,(62)(63)(64), the endoplasmic reticulum stress and unfolded protein response gene CHOP/DDIT3 (C/EBP homologous protein/ DNA damage-inducible transcript 3) (65), and sonic hedgehog receptor Patched (PTCH1) (66). In contrast, down-regulated targets included the epidermal growth factor receptor (EGFR) (67) and the low density lipoprotein receptorrelated protein 1 (LRP1) (68). Although not formally defined as direct targets, the glycogen synthase kinase3␤ (GSK3␤) (59,69,70), APP (59) itself, and BACE1 (59) are considered AICD-regulated genes.…”
Section: Aicd A␤42 and Tau Interactions With Dnamentioning
confidence: 99%